Preventing Foodborne Illness: Bacillus cereus - Keith R. Schneider; Renée Goodrich Schneider; Rachael Silverberg (EDIS, 2015)
Ingesting foods contaminated with Bacillus cereus bacteria can lead to nausea, vomiting, abdominal cramps, and diarrhea. Though B. cereus is commonly found in many types of fresh and processed foods, proper cooking, handling, and storage can minimize the risk of contamination. This 5-page fact sheet explains how B. cereus is transmitted, what foods it is commonly associated with, the methods used to prevent contamination, and good practices for receiving, handling, processing, and storing food. Written by Keith R. Schneider, Renée Goodrich Schneider, and Rachael Silverberg, and published by the UF Department of Food Science and Human Nutrition, August 2015.